2010
DOI: 10.1016/j.ceb.2009.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Role of autophagy in suppression of inflammation and cancer

Abstract: Autophagy is a crucial component of the cellular stress adaptation response that maintains mammalian homeostasis. Autophagy protects against neurodegenerative and inflammatory conditions, aging, and cancer. This is accomplished by the degradation and intracellular recycling of cellular components to maintain energy metabolism and by damage mitigation through the elimination of damaged proteins and organelles. How autophagy modulates oncogenesis is gradually emerging. Tumor cells induce autophagy in response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
226
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(236 citation statements)
references
References 48 publications
9
226
0
1
Order By: Relevance
“…Autophagy is a crucial component of the cellular stress adaptation response (White et al, 2010), and its pathways have been demonstrated to play a key role in fine-tuning inflammatory responses in keratinocytes (Fésüs et al, 2011). Mitochondria play a central role in the initiation of inflammasomes and other inflammatory pathways (Green et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is a crucial component of the cellular stress adaptation response (White et al, 2010), and its pathways have been demonstrated to play a key role in fine-tuning inflammatory responses in keratinocytes (Fésüs et al, 2011). Mitochondria play a central role in the initiation of inflammasomes and other inflammatory pathways (Green et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…8 Autophagy has emerged as a homeostatic mechanism regulating the turnover of long-lived or damaged proteins and organelles, and buffering metabolic stress induced under starvation conditions by recycling intracellular constituents. 9 Autophagosomes engulfing organelles then fuse with lysosomes and mature into autolysosomes.…”
mentioning
confidence: 99%
“…Although previous findings strongly suggest that autophagy contributes to sustainable cell survival, antitumorigenic roles of autophagy have been also mentioned. 8 Autophagy has roles in protecting cells against shortage of nutrients. Cells supply amino acids from self-digested organelles as an alternative energy source for their survival.…”
mentioning
confidence: 99%
“…With the "MetaDE" package of R project, we merged the three expression profiles and screened the differentially- pathway-gene information, we constructed an ARP [13] complex network. Four topological properties (degree, average shortest path length, closeness centrality, and clustering coeffi cient of the ARP network) were analyzed by the "network analyzer" plugin in Cytoscape software (www.…”
Section: Gene Expression Signifi Cance Analysismentioning
confidence: 99%
“…Cerebral ischemia-induced microglial autophagy contributes to ischemic neuronal inflammation and injury. Autophagy is a process for the intracellular bulk degradation of cellular constituents that has multiple effects on immunity [12][13][14] . Blocking autophagy in epithelial cells enhances host cell death and finally leads to tissue destruction and infl ammation [15] .…”
Section: Introductionmentioning
confidence: 99%